Insights into the structure and drug design of benzimidazole derivatives targeting the epidermal growth factor receptor (EGFR) - Abdullah, Mar'iyah Najihah; Ali, Yousaf; Abd Hamid, Shafida (Wiley, 2022)
Tyrosine kinase overexpression could result in an unfavourable consequence of cancer progression in the body. A number of kinase inhibitor drugs targeting various cancer-related protein kinases have been developed and proven successful in clinical therapy. Benzimidazole is one of the most studied scaffolds in the search for effective anticancer drugs. The association of various functional groups and the structural design of the compounds may influence the binding towards the receptor. Despite numerous publications on the design, synthesis and biological assays of benzimidazole derivatives, their inhibitory activities against epidermal growth factor receptor (EGFR), a receptor tyrosine kinase (RTK), have not been specifically analysed. This review covers recent research reports on the anticancer activity of benzimidazole derivatives focusing on EGFR expression cell lines, based on their structure-activity relationship study. We believe it would aid researchers to envision the challenges and explore benzimidazole's potentials as tyrosine kinase inhibitors.